Fabrication of Axial and Radial Heterostructures for Semiconductor Nanowires by Using Selective-Area Metal-Organic Vapor-Phase Epitaxy. (29th August 2011) - Hiruma, K.; Tomioka, K.; Mohan, P.; Yang, L.; Noborisaka, J.; Hua, B.; Hayashida, A.; Fujisawa, S.; Hara, S.; Motohisa, J.; Fukui, T.
Abstract : The fabrication of GaAs- and InP-based III-V semiconductor nanowires with axial/radial heterostructures by using selective-area metal-organic vapor-phase epitaxy is reviewed. Nanowires, with a diameter of 50–300 nm and with a length of up to 10  μ m, have been grown along the〈 111 〉 B or〈 111 〉 A crystallographic orientation from lithography-defined SiO2 mask openings on a group III-V semiconductor substrate surface. An InGaAs quantum well (QW) in GaAs/InGaAs nanowires and a GaAs QW in GaAs/AlGaAs or GaAs/GaAsP nanowires have been fabricated for the axial heterostructures to investigate photoluminescence spectra from QWs with various thicknesses. Transmission electron microscopy combined with energy dispersive X-ray spectroscopy measurements have been used to analyze the crystal structure and the atomic composition profile for the nanowires. GaAs/AlGaAs, InP/InAs/InP, and GaAs/GaAsP core-shell structures have been found to be effective for the radial heterostructures to increase photoluminescence intensity and have enabled laser emissions from a single GaAs/GaAsP nanowire waveguide. The results have indicated that the core-shell structure is indispensable for surface passivation and practical use of nanowire optoelectronics devices.